Organocatalytic Asymmetric Aldol Reactions in Aqueous or Neat Conditions: Review of Data Published in 2009-2013 - Bartok, Mihaly; Dombi, Gyorgy (Current Green Chemistry, 2014)
The aim of this review was to collect the results published in 2009-2013 on asymmetric aldol reactions taking place in aqueous media (water, brine) and in the absence of solvents (neat), to highlight the catalysts identified as best, and, in the course of doing so, to present the trends of research in this field. The five groups of organocatalysts discussed are: 1. Amino acids and esterified hydroxyamino acids; 2. Carboxamides of amino acids; 3. Peptides and derivatives; 4. Peptide-based alcohols; 5. 1, 2-Diamines and derivatives. The efficiency of the catalysts is characterized by their concentration in the reaction, reaction time, their selectivity (anti/syn) and their enantioselectivity.
Keywords: hydroxyamino acid